Cyfrowe metamorfozy, czyli słów kilka o Owidiuszu w serwisie YouTube. Rekonesans - Dominas, Konrad (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2023)
The article is an attempt to classify and analyse videos dedicated to Ovid on YouTube. This text can be treated as a broad introduction to research on Greco–Roman heritage in the space of social media. The review of the materials presented here clearly shows that YouTube has three basic functions in this context: 1) as a space for publishing and sharing materials about the poet from Sulmona; 2) as an educational or quasi–educational platform; 3) as a place for the reception of the work and life of Ovid. In addition, these examples not only supplement the traditional knowledge about the author of Metamorphoses, but also an important point of reference, one of the artifacts responsible for the changes that take place in the understanding and perception of ancient culture in the postmodern world.